(untitled) (Bangladesh Journal of Medical Science, 2012)
Background: Traditionally, enteric feeds are withheld for a period of 48-72 hrs, sometimes even more following enteric anastomosis depending upon return of full peristaltic sounds. This results in a period of nonstimulation of gut Gut Rest, which was supposed to result in better anastomotic healing. But this same also deprives the intestinal mucosa of surface nutrients as well as prolongs parenteral fluid therapy, thereby depriving the patients of adequate nutrition. Along with it, prolonged parenteral therapy also keeps the patients bound to bed with its resultant complications like, prolonged hospital stay and increased cost of therapy. Objectives: To compare the benefits of early enteral feeding over conventional enteric feeding following enteric anastomosis with special regards to patients recovery and complications. Methods and materials: The selection of patients into group A (60) and group B (60) was done after having fulfilled inclusion and exclusion criteria. Informed consent was obtained. The patients of group A were fed via enteral route within 24 hrs of enteric anastomosis. The patients of group B were fed via enteral route after 48-72 hrs or appearance of full peristaltic sounds following enteric anastomosis. These patients were followed in post operative period for their drain output, any nausea, vomiting or significant abdominal distension, prolonged ileus, post operative duration of shospital stay, post operative infective complications (e.g. wound infection, UTI, RTI), and different haematological and biochemical examinations. Results: This study shows that post operative nausea-vomiting, anastomotic leakage rate, re-exploration, wound infection and RTI rates are higher in group A than those of group B. In this study, the incidence of UTI in post operative period is higher in group B. But the differences in above mentioned variables are not statistically significant. Whereas appearance of intestinal peristaltic sound is earlier in group A (42.8 ± 10.68 hours) compare to that of group B (52.6 ± 13.46 hours). Here, the difference is statistically significant (p value = 0.000022) The duration of post operative hospital stay is shorter in group A (8.45 ± 5.143 days) than that of group B (10.533 ± 4.952 days). The difference of duration post operative hospital stay is statistically significant (p value = 0.0257). Removal of nasogastric tube, resumption of oral feeding, and passage of first flatus and/or defecation were earlier in the group A than that of the group B; the differences were statistically significant. The post operative day-5 albumin level is better in group A (3.147 ± 0.4409 gm/dl) than that of group B (2.935 ± 0.3124 gm/dl). This difference is also statistically significant (p value = 0.0029). There are three mortalities in group Awhereas one mortality in group B. This difference in mortality in two groups is not statistically significant. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12597 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12